2005
DOI: 10.1161/01.atv.0000181763.57495.2b
|View full text |Cite
|
Sign up to set email alerts
|

Iron Chelation Suppresses Ferritin Upregulation and Attenuates Vascular Dysfunction in the Aorta of Angiotensin II–Infused Rats

Abstract: Objective-We have investigated whether long-term administration of angiotensin (Ang) II causes ferritin induction and iron accumulation in the rat aorta, and their possible relation to regulatory effects on gene expression and vascular function in Ang II-infused animals. Methods and Results-Sprague-Dawley rats were given Ang II for 7 days via subcutaneously implanted osmotic minipumps. Ang II infusion caused a Ͼ20-fold increase in ferritin protein expression over control values. Immunohistochemistry showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 50 publications
(47 reference statements)
1
38
0
Order By: Relevance
“…This can occur through enhancement of oxidative stress by iron-catalyzed hydroxyl radical formation, via Fenton chemistry, and subsequent lipid peroxidation. 31 The current work is the first demonstration that Ang II treatment can cause iron accumulation in AAA in an apoEdeficient mouse model and that AR9276 can reduce this iron accumulation.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…This can occur through enhancement of oxidative stress by iron-catalyzed hydroxyl radical formation, via Fenton chemistry, and subsequent lipid peroxidation. 31 The current work is the first demonstration that Ang II treatment can cause iron accumulation in AAA in an apoEdeficient mouse model and that AR9276 can reduce this iron accumulation.…”
Section: Discussionmentioning
confidence: 76%
“…One interesting finding in the present study is iron accumulation in the intima and adventitia of Ang II-induced AAA. Iron accumulation, which has been reported in humans 30 and in an Ang II-treated rat model, 31 may exacerbate Ang II-induced vascular damage. This can occur through enhancement of oxidative stress by iron-catalyzed hydroxyl radical formation, via Fenton chemistry, and subsequent lipid peroxidation.…”
Section: Discussionmentioning
confidence: 87%
“…The following respective sense and antisense primers were used: 5′-AAGTCCTGCTGAGCGAAGAT-3′ and 5′-TGGTCCCTA AATGCAGTCTG-3′ for IRE(+)DMT1; 5′-TCTACCTCC TGAACACCGTG-3′ and 5′-CGTTAGCTTTACCCGACT CC-3′ for IRE(−)DMT1; 5′-CCAGATTATGACATTCGGT-3′ and 5′-TTGGCTCAGTATCTTTAGGT-3′ for FPN; and 5′-GGCAACAGACGAGACAGACT-3′ and 5′-ATGCAA CAGAGACCACAGGA-3′ for hepc. The primers used for TfR and GAPDH have been described previously (19). The mRNA expression of these genes was normalized to GAPDH mRNA expression and is presented here as the percentage of the values from the aortas of untreated animals.…”
Section: Rna Extraction Northern Blot Analysis and Real Time Rt-pcrmentioning
confidence: 99%
“…Alterations of the miR-122/CCL2 pathway may account for the inability of Vit.E to alleviate IO-induced hepatic inflammation because Vit.E intervention had no effect on the miR-122/CCL2 pathway. It has been reported that the intracellular iron content may affect the CCL2 expression in neuroblastoma and astrocytoma cell lines [24], rat aorta [25] and heart tissues [26], and mice cardiovascular systems [27]. Otogawa et al used an acute liver injury model that is induced by thioacetamide [28].…”
Section: Discussionmentioning
confidence: 99%